2020
DOI: 10.1080/23311932.2020.1747854
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rhizobial inoculants and micronutrients on yield and yield components of faba bean (Vicia faba L.) on vertisol of Wereillu district, South Wollo, Ethiopia

Abstract: Nitrogen fixation by legumes like faba bean is a cheap way of fixing atmospheric nitrogen to plant available form. However, the inoculation of grain legumes with rhizobium bacteria along with the addition of micronutrients is poorly researched in Amhara Region of Ethiopia. Thus a study to examine the effects of rhizobium leguminosarum (var vicae) strains and micronutrients on nodulation, growth, and yield of faba bean was conducted in Wereillu district of Amhara Region, Ethiopia during the rainy season of 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
3
4
0
Order By: Relevance
“…Higher nodule weights were further observed for the light variety compared to ICCV3203 and ICCV3110 genotypes of chickpea. This is consistent with previous reports such as those conducted on faba bean in Ethiopia [75] and chickpea in Tunisia and Ethiopia [76,77], where inoculation with different strains yielded varying nodule numbers and weights. Moreover, varying effects of the Mesorhizobium strains on the shoot dry weights, average heights, and symbiotic efficiencies of different chickpea genotypes were observed.…”
Section: Discussionsupporting
confidence: 93%
“…Higher nodule weights were further observed for the light variety compared to ICCV3203 and ICCV3110 genotypes of chickpea. This is consistent with previous reports such as those conducted on faba bean in Ethiopia [75] and chickpea in Tunisia and Ethiopia [76,77], where inoculation with different strains yielded varying nodule numbers and weights. Moreover, varying effects of the Mesorhizobium strains on the shoot dry weights, average heights, and symbiotic efficiencies of different chickpea genotypes were observed.…”
Section: Discussionsupporting
confidence: 93%
“…This confirms the effective role of micronutrients and their effect on the symbiotic fixation of nitrogen. This results was in line with the study of Adissie et al (2020) whom reported that inoculation of faba bean with both strain and micronutrients could increase seeds No./ plant and 100-seed weight. The highest seeds No./ plant and 100seed weight produced by RhM+Pm treatment (T9) may be attributed to its ability to enhanced utilization of growth factors, and improved nodule development, metabolic processes, easy availability of nutrients and root growth.…”
Section: -Yield Components *Seeds No/plantand 100-seed Weightsupporting
confidence: 92%
“…Inoculation with rhizobium produced significantly taller soybean plants (53.4 cm) compared to that (48.9 cm) of un-inoculated plants at the same stage (Lamptey et al, 2014). The results are in accordance with those of Adissie et al (2020) and Ben et al (2019). T9) that are associated with increasing availability of nutrients and their uptake during the early stages and improving meristematic expansion surface area of the leaves and physiological activates in the plants.…”
Section: -Growth Parameters * Plant Heightsupporting
confidence: 90%
See 1 more Smart Citation
“…For example, the same isolate of fungi can be beneficial on some plant genotypes (Oliveira et al, 2017;Garg and Singh, 2018;Le Pioufle et al, 2019), negative on others (Janoušková et al, 2013;Symanczik et al, 2015;Loján et al, 2017), or have no effect on yet others (Rosa et al, 2020). This is particularly true for microbes with strict host requirements, such as rhizobia (Rebah et al, 2002;Sanz-sáez et al, 2015;Adissie et al, 2020). Whatever the outcome, the connection between plant performance and SMC diversity is paramount to ecosystem stability and resilience.…”
Section: Does Inoculation Affect Plant Performance?mentioning
confidence: 99%